2020
DOI: 10.1021/acsaem.0c00426
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4 Hollow Porous Nanospheres with Oxygen Vacancies for Enhanced Li–O2 Batteries

Abstract: Creating oxygen vacancies to tune the surface electronic structure is a feasible approach to enhance the electrocatalytic activities of noble-metal-free transition-metal oxides for Li−O 2 batteries. Herein, vacancy-rich Co 3 O 4 hollow porous nanospheres have been obtained through a facile reduction strategy from Co 3 O 4 hollow porous nanospheres, which were prepared in a self-template construction manner through a solvothermal synthesis followed by a heat treatment. The reduced Co 3 O 4 hollow porous nanosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…By contrast, the bismuth NPs in the 550‐Bi@N‐CNCs (Supporting Information, Figure S22; Movie S4) and 700‐Bi@N‐CNCs (Supporting Information, Figure S23; Movie S5) are both broken and seriously agglomerated after the depotassiation process. The comparative real‐time observations here visualize the superior structural reversibility of the 850‐Bi@N‐CNCs, which ensures the formation of a stable yet thin SEI layer on the outer robust N‐CNCs, [31–34] and a close electronic contact between the continuous carbon network and Bi NPs meantime [35–37] . While for the 550‐Bi@N‐CNCs or 700‐Bi@N‐CNCs, the repetitive rupturing and reformation of the passivating SEI film occur, and always convert the cyclable K species in electrode sur‐/interfaces to dead K in the SEI, eventually leading to the death of the batteries due to the K exhaustion.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…By contrast, the bismuth NPs in the 550‐Bi@N‐CNCs (Supporting Information, Figure S22; Movie S4) and 700‐Bi@N‐CNCs (Supporting Information, Figure S23; Movie S5) are both broken and seriously agglomerated after the depotassiation process. The comparative real‐time observations here visualize the superior structural reversibility of the 850‐Bi@N‐CNCs, which ensures the formation of a stable yet thin SEI layer on the outer robust N‐CNCs, [31–34] and a close electronic contact between the continuous carbon network and Bi NPs meantime [35–37] . While for the 550‐Bi@N‐CNCs or 700‐Bi@N‐CNCs, the repetitive rupturing and reformation of the passivating SEI film occur, and always convert the cyclable K species in electrode sur‐/interfaces to dead K in the SEI, eventually leading to the death of the batteries due to the K exhaustion.…”
Section: Resultsmentioning
confidence: 78%
“…Moreover,a fter 20 potassiation/ depotassiation cycles,t he well-defined 850-Bi@N-CNCs still can maintains its structural integrity without noticeable structure rupture (Supporting Information, Movie S3), which authenticates that the internal void space and elastic shell of N-CNCs can effectively relieve the volume expansion of Bi NPs.B yc ontrast, the bismuth NPs in the 550-Bi@N-CNCs (Supporting Information, Figure S22;M ovie S4) and 700-Bi@N-CNCs (Supporting Information, Figure S23;Movie S5) are both broken and seriously agglomerated after the depotassiation process.T he comparative real-time observations here visualize the superior structural reversibility of the 850-Bi@N-CNCs,which ensures the formation of astable yet thin Angewandte Chemie Forschungsartikel SEI layer on the outer robust N-CNCs, [31][32][33][34] and ac lose electronic contact between the continuous carbon network and Bi NPs meantime. [35][36][37] While for the 550-Bi@N-CNCs or 700-Bi@N-CNCs,the repetitive rupturing and reformation of the passivating SEI film occur, and always convert the cyclable Ks pecies in electrode sur-/interfaces to dead Ki n the SEI, eventually leading to the death of the batteries due to the Ke xhaustion.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Research Articles SEI layer on the outer robust N-CNCs, [31][32][33][34] and ac lose electronic contact between the continuous carbon network and Bi NPs meantime. [35][36][37] While for the 550-Bi@N-CNCs or 700-Bi@N-CNCs,the repetitive rupturing and reformation of the passivating SEI film occur, and always convert the cyclable Ks pecies in electrode sur-/interfaces to dead Ki n the SEI, eventually leading to the death of the batteries due to the Ke xhaustion.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The catalytic active site could be created by defect engineering strategy, including the control of Co 2+ /Co 3+ ratio and the introduction of oxygen/cationic vacancies, which causes the activation and partial dissociation of O O bonds during the oxygen adsorption process. The main methods of manufacturing defects are summarized as follows: the use of chemical reduction, 15,18 changing the heat-treatment temperature, 44,78 incorporating metals or metal oxides, and so on. 20,23,31 In 2015, Song et al 96 found that the Co 3+ active site plays an even greater role in comparison with Co 2+ , which determines the adsorption properties of reactants, as shown in Figure 5A.…”
Section: Defect Engineeringmentioning
confidence: 99%